The hunt is on - Jun, Nie, 1975- (Seekers of the Aweto, 2021)
"Xinyue and his brother are seekers, hunting Aweto--a rare, plantlike treasure--along the Silk Road. When Xinyue discovers the child of a deity that creates Aweto, it disrupts his already turbulent life."--